Develop IR decoder with alarm using PIC16F84A MCU / Marziatul Akhtar Saleh - Saleh, Marziatul Akhtar (2006)
Microcontroller is an ideal chip that we can program to control things that we can electronically imagine or speaking of. The Infrared (IR) Decoder Prototype with Alarm using PIC16F84A is intended to decode to signal transmitted by remote control. When the button on the remote control is pressed, the signal is retrieved by the infrared detector. Infrared detector will then send the input signal to the microcontroller. Microcontroller will omit the output on the 7-segment display. In real life implementation, the output that the microcontroller instructs to operate will be appliances such as lights and fans. If an error occur or in other words if the button that has been pressed is not defined in the program, microcontroller will send signal to buzzer to emit beeper sound to alert that there is an error occur.